The Law Is (Not) for Kids, Second Edition A Legal Rights Guide for Canadian Children and Teens - Lecic, Ned (Athabasca University Press, 2023)
Since its publication in 2019, this important and practical guide to the law has empowered and educated Canadian children and youth and those who serve them. The authors address questions about how rights and laws affect the lives of young people at home, at school, at work, and in their relationships as they draw attention to the many ways in which a person's life can intersect with the law. This revised and updated edition reflects the progress that has occurred in Indigenous child welfare legislation. Updates also reflect amendments to the Youth Criminal Justice Act and the Divorce Act as well as amendments to a variety of provincial child and family laws.